Fatigue and Failure Analysis of Sandwich Composites using Two Types of Cross-Ply Glass Fibers Laminates and Epoxy Resin - Monteiro Cheloni, João Pedro; Silveira, Marcio Eduardo; Najar Lopes, Eder Sócrates; da Silva, Leandro José (Journal of Research Updates in Polymer Science, 2022)
Sandwich structures have become effective structural elements for engineering applications due to their good design flexibility. Understanding the material behavior under static and dynamic loads, as well as the failure mechanisms of these sandwich structures, is of great importance. This work evaluates the fatigue and static bending behavior of epoxy resin specimens and sandwich composites composed of an epoxy resin core with glass fiber laminated faces. The fatigue life, failure modes, and stiffness degradation of these specimens are determined experimentally. The specimens were cycled under constant amplitude and monitored by a data acquisition system that allowed continuous data collection. Three stages of failure were identified using microscope analyses and stiffness degradation curves. In the case of an imposed displacement of 2 mm, the sandwich structures were shown to have a significantly lower fatigue life than the epoxy resin specimens.